PTH-009 New Generation High Definition Colonoscopes Increase Adenoma Detection within The Bowel Cancer Screening Programme. (17th August 2016) - Bond, A; Fisher, G; Subramanian, S; O'Toole, P; Haslam, N; Probert, C; Cox, T; Sarkar, S
Abstract : Introduction: Adenoma detection rate (ADR) is the most important quality indicator for screening colonoscopy, due to its association with colorectal cancer outcomes. As a result a number of techniques and technologies have been proposed that have the potential to improved ADR. The aim of this study was to assess the potential impact of the new generation high definition colonoscopies (Olympus LUCERA ELITE H290) on ADR within the Bowel Cancer Screening Programme (BCSP) in one UK centre. Methods: This was a retrospective observational study in patients undergoing an index screening colonoscopy within the Liverpool & Wirral BCSP. The examination was performed with either the standard definition (SD) colonoscopes (Olympus 240/260 series) or the high definition (HD) colonoscope (Olympus H290 system) with the primary outcome measure of ADR and mean adenoma per procedure (MAP) between the 2 groups. Logistic regression modelling was used to assess the impact of variable on ADR. Results: 395 patients (60.5% male, mean age 66.8 years) underwent screening colonoscopy with 45% performed with HD colonoscopies. A caecal intubation rate of 97.5% was recorded. The mean mean adenoma per procedure (MAP) in the HD groups was 2.1 (+/-±2.0), whilst in the SD group it was 1.6 (+/-±1.8) (p = 0.01). The overall ADR for the 394 patients was found to be 68.6%. ADR with SD was 63.13%, compared to 75.71% with HD (p = 0.007). There was no significant difference in withdrawal time. In the logistic regression only the high definition scopes (p = 0.03) and male gender (p = 0.04) was found to impact upon ADR. Conclusion: Whilst it's established males have greater adenoma burden then females, our study has highlighted the impact of the new generation High Definition colonoscope (H290 Series) on improving adenoma detections rates, thus potentially improving long-term outcomes within the BCSP. Disclosure of Interest: None Declared